2015
DOI: 10.1128/jcm.01033-15
|View full text |Cite
|
Sign up to set email alerts
|

First Case of Human Cerebral Taenia martis Cysticercosis

Abstract: Taenia martis is a tapeworm affecting mustelids, with rodents serving as intermediate hosts. The larval stage (cysticercus) has been found before only rarely in humans or primates. We hereby describe a case of cerebral T. martis cysticercosis in a French immunocompetent patient, confirmed by DNA analyses of biopsy material. CASE REPORT In January 2012, a 44-year-old woman with no significant medical history except Verneuil's disease was admitted to the Strasbourg University Hospital for right hemiparesis and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
0
27
0
2
Order By: Relevance
“…Rare cases of carnivore-transmitted cysticercosis caused by, for example, T. crassiceps ( Heldwein et al., 2006 , Flammer et al., 2014 ) and T. martis ( Brunet et al., 2015 , Eberwei et al., 2013 ), have been documented in people in Europe. Furthermore, several lethal T. martis ( Brunet et al., 2014 , De Liberato et al., 2014 ) and T. crassiceps infections were reported recently for lemurs in zoos ( Luzon et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rare cases of carnivore-transmitted cysticercosis caused by, for example, T. crassiceps ( Heldwein et al., 2006 , Flammer et al., 2014 ) and T. martis ( Brunet et al., 2015 , Eberwei et al., 2013 ), have been documented in people in Europe. Furthermore, several lethal T. martis ( Brunet et al., 2014 , De Liberato et al., 2014 ) and T. crassiceps infections were reported recently for lemurs in zoos ( Luzon et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 Human infection with T. martis, where the human serves as dead-end intermediate host, is very rarely seen and only two cases have been reported so far. 4,5 In 2010, the first described human infection with larval T. martis had occurred in a 43-year-old woman living in a small village in southwest Germany. 4 The patient had complained of flashing light sensations in her left eye, and a T. martis larva had been found subretinally similar to our case.…”
Section: Discussionmentioning
confidence: 99%
“…The second human infection with T. martis had been diagnosed in 2012 in a 44-year-old woman in eastern France. 5 A single lesion had developed in the left temporal lobe of the brain, causing aphasia and hemiparesis. The parasite had been removed surgically and an oral antiparasitic regimen with albendazole and praziquantel had been administered, leading to full recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brunet et al reported neurocysticercosis due to Taenia martis in an immunocompromised host. In fact, Taenia martis has been described in human beings for a few years but not in brain (3). The new species cerebral neurocysticercosis is an actual challenge.…”
Section: Dear Editormentioning
confidence: 99%